1988
DOI: 10.1128/jvi.62.9.3301-3308.1988
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of in vivo-selected viral variants causing chronic infection: importance of mutation in the L RNA segment of lymphocytic choriomeningitis virus

Abstract: Viral variants with different biological properties are present in the central nervous systems (CNS) and lymphoid tissues of mice persistently infected with lymphocytic choriomeningitis virus (LCMV). Viral isolates from the CNS are similar to the original Armstrong LCMV strain and induce potent virus-specific T-cell responses in adult mice, and the infection is rapidly cleared. In contrast, LCMV isolates derived from spleens of carrier mice cause persistent infections in adult mice. This chronic infection is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Clone 13 differs from its parent virus Armstrong at only two amino acid positions, one in the virus glycoprotein GP-1 and the other in the putative viral polymerase L (56,58). While the polymerase change contributes to the immunosuppressive phenotype (3,37), likely by giving clone 13 a replicative advantage over Armstrong, only the phenylalanine (Armstrong) to leucine (clone 13) change in GP-1 is consistently associated with the immunosuppressive phenotype (1,56). There is strong evidence indicating that GP-1 is the virion attachment protein that mediates binding to cell surface receptors for LCMV (9,51,67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clone 13 differs from its parent virus Armstrong at only two amino acid positions, one in the virus glycoprotein GP-1 and the other in the putative viral polymerase L (56,58). While the polymerase change contributes to the immunosuppressive phenotype (3,37), likely by giving clone 13 a replicative advantage over Armstrong, only the phenylalanine (Armstrong) to leucine (clone 13) change in GP-1 is consistently associated with the immunosuppressive phenotype (1,56). There is strong evidence indicating that GP-1 is the virion attachment protein that mediates binding to cell surface receptors for LCMV (9,51,67).…”
Section: Discussionmentioning
confidence: 99%
“…The virus isolates used are closely related in that the immunosuppressive LCMV isolate (clone 13) was derived from the spleen of a mouse persistently infected from birth with the nonsuppressive LCMV Armstrong 53b isolate (2), and differs from it at only two amino acid positions, amino acid 260 in the virus glycoprotein GP-1 and amino acid 1079 in the viral polymerase protein, L (1,56,58). Sequence analysis of a panel of independently-isolated immunosuppressive variants derived from Armstrong-infected mice has shown that only the amino acid change in GP-1 is consistently associated with the immunosuppressive phenotype (1,56), while reassortant analysis suggests that the L RNA sequence also affects the biological properties of the virus (3,37).…”
mentioning
confidence: 99%
“…CTL assays. Primary and secondary LCMV-specific CTL responses in spleens and lymph nodes were determined by a 6-h 51 Cr release assay as described previously (4,5).…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of a viral infection depends on a critical balance between the extent of viral spread and replication and the magnitude of the host's immune response. We have been studying infection of mice with lymphocytic choriomeningitis virus (LCMV) as a model system to understand the host and viral determinants that lead to viral clearance or persistence (2,4,5,20). Infection of immunocompetent adult mice with the Armstrong strain of LCMV induces a potent antiviral T-cell response, and virus is eliminated within 2 weeks.…”
mentioning
confidence: 99%